Pengaruh Penggunaan Qris Terhadap Kemudahan Dan Kepuasan Masyarakat Di Toko Sahabat Kosmetik - Syaripa; Dini Arianti; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the effect of using the Quick Response Code Indonesian Standard (QRIS) on transaction convenience and customer satisfaction at Sahabat Kosmetik Store. The research uses a quantitative approach with a survey method involving 60 respondents who have used QRIS for transactions. Data were collected through a questionnaire with a five-point Likert scale and analyzed using validity tests, reliability tests, and multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that the use of QRIS has a positive and significant effect on transaction convenience and customer satisfaction. Further analysis shows that transaction convenience plays a role as a partial mediating variable in the relationship between QRIS usage and public satisfaction. This study concludes that the implementation of QRIS can improve transaction convenience and public satisfaction, making it an effective digital payment strategy for business actors.